2010
DOI: 10.1093/nar/gkq115
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intragenic CpG content on gene expression

Abstract: The development of vaccine components or recombinant therapeutics critically depends on sustained expression of the corresponding transgene. This study aimed to determine the contribution of intragenic CpG content to expression efficiency in transiently and stably transfected mammalian cells. Based upon a humanized version of green fluorescent protein (GFP) containing 60 CpGs within its coding sequence, a CpG-depleted variant of the GFP reporter was established by carefully modulating the codon usage. Interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 66 publications
6
76
0
1
Order By: Relevance
“…On a smaller scale, optimizing codons of individual proteins can lead to increased protein expression, but the mechanism(s) underlying the increased protein remains controversial. Several groups have reported that the protein increase results from an increase in the rate of translation (26,27), whereas others have observed an increase in the rate of transcription (28,29). Furthermore, a recent study concluded that, although transcriptional control is the broadest means of controlling protein expression, a fraction of proteins are differentially regulated at the translational level (30).…”
Section: Significancementioning
confidence: 99%
“…On a smaller scale, optimizing codons of individual proteins can lead to increased protein expression, but the mechanism(s) underlying the increased protein remains controversial. Several groups have reported that the protein increase results from an increase in the rate of translation (26,27), whereas others have observed an increase in the rate of transcription (28,29). Furthermore, a recent study concluded that, although transcriptional control is the broadest means of controlling protein expression, a fraction of proteins are differentially regulated at the translational level (30).…”
Section: Significancementioning
confidence: 99%
“…The molecular mechanism underlying CpG-mediated transcriptional regulation is currently unknown, but has been reproducible for a diverse panel of genes and might be associated with sequence-specific differences in nucleosomal positions, as we have recently reported. 27 The negative effects of CpG depletion on mEPO expression in vivo, which were particularly evident at higher pDNA doses might have future implications for rational transgene design. Interestingly, our in vitro experiments have indicated that the expression of codonoptimized genes can be further augmented by inserting additional CpGs into the coding region.…”
Section: Impact Of Gene Design On Long-term Transgene Expression D Komentioning
confidence: 99%
“…27 For western blot analysis, 40 mg of total protein from both fractions were separated by 12.5% sodium dodecyl sulfate (SDS) polyacrylamide gel electrophoresis. Erythropoietin was detected using a specific mouse monoclonal antibody (1:500; R&D Systems) and a streptavidin alkaline-phosphatase-conjugated antibody (1:10 000; Roche) followed by staining with the chromogenic substrate NBT/BCIP (Roche).…”
Section: Analysis Of Mepo Expression In Vitromentioning
confidence: 99%
See 2 more Smart Citations